Unhealthy Lifestyle Habits and Implications of Adolescent Obesity Southeast Asia: Literature Review - Annisa, Putri; Muntaz, Maharani; Sinaga, Rismauli Romaito; Handayani, Dwi Septia; Herbawani, Chahya Kharin (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Obesity among children and adolescents has become a serious global health problem. This is demonstrated by WHO data with child and adolescent obesity rates in Southeast Asia increasing with the prevalence of obesity ranging from 31% in Southeast Asia. This study aims to explore current scientific evidence that can inform the formulation of more effective adolescent obesity prevention and intervention strategies in the region. Between 2020-2024, searches were sourced from Google Scholar and Pubmed, using Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) with exclusion criteria, and 8 relevant articles were obtained for analysis. The results showed that the increasing prevalence of adolescent obesity in Southeast Asia is evidenced by several contributing factors including, lack of physical activity due to gadgets, parental roles, poor diet, and family and socioeconomic environments that limit access to health. It was concluded that the lack of physical activity due to gadgets, the role of parents, poor diet, family’s role and socio-economic environment that limits access to health are factors that cause adolescent obesity. Integrated efforts need to be made through nutrition and physical activity education since school age, empowering the role of parents in shaping healthy eating patterns at home, and providing facilities that encourage active lifestyles.